Comparative Transcriptomics Analysis and Functional Study Reveal Important Role of High-Temperature Stress Response Gene GmHSFA2 During Flower Bud Development of CMS-Based F1 in Soybean - Ding, Xianlong; Guo, Qingling; Li, Qiang; Gai, Junyi; Yang, Shouping (Frontiers in Plant Science, 2020)
High-temperature (HT) is one of the most important environmental factors that negatively impact the yield of some soybean cytoplasmic male sterility (CMS)-based hybrid (F1) combinations. The response of soybean to HT, especially at the male organ development stage, is poorly understood. To investigate the molecular mechanisms of the response from soybean CMS-based F1 male organ to HT, a detailed transcriptomics analysis was performed during flower bud development of soybean HT-tolerant and HT-sensitive CMS-based F1 combinations (NF1 and YF1) under normal-temperature and HT conditions. Obvious HT damage was observed by subjecting YF1 with HT, such as indehiscent anthers and decreased pollen fertility, whereas the male fertility of NF1 was normal. In total, 8,784 differentially expressed genes (DEGs) were found to respond to HT stress, which were mainly associated with anther/pollen wall development, carbohydrate metabolism and sugar transport, and auxin signaling. The quantitative real-time PCR (qRT-PCR) analysis and substance content detection also revealed that HT caused male fertility defects in YF1 by altering pectin metabolism, auxin, and sugar signaling pathways. Most importantly, the sugar signaling-PIF-auxin signaling pathway may underlie the instability of male fertility in YF1 under HT. Furthermore, HT induced the expression of heat shock factor (HSF) and heat shock protein (HSP) gene families. Overexpression of GmHSFA2 in Arabidopsis can promote the expression of HT protective genes (such as HSP20) by binding to the HSE motifs in their promoters, so as to improve the HT tolerance during flowering. Our results indicated that GmHSFA2 acted as a positive regulator, conferring HT tolerance improvement in soybean CMS-based F1. GmHSFA2 may be directly involved in the activation of male fertility protection mechanism in the soybean CMS-based F1 under HT stress.